Design and development of a steady state close-cycle aquaculture system for intensive culture of fresh water fish species - Md Asaduzzaman (Fakulti Agroteknologi dan Sains Makanan, 2011)
This study was to design and develop a steady-state conditioned closecycle aquaculture system to provide a conducive culture environment for intensive culture of fresh water fish species. Four major experiments were conducted to assess the efficiency of the system with varying ratios of volume of the fish rearing unit and volume of the biological filter (Aerobic) of 45:1, 23:1, 10:1 and 5:1 for the Experiment 1, Experiment 2, Experiment 3 and Experiment 4, respectively.